China Business 2.0 : Analyze the Economy, Understand the Society, and Manage Effectively - Randau, Henk R.; Medinskaya, Olga (Management for Professionals,, 2015)
China is entering a new stage of economic and societal development, called China 2.0, a new era that is characterized by China's diminishing low-cost advantage and increased local competition. Succeeding in the China 2.0 era will require western managers to reposition their businesses. Inspired by their extensive experience in doing business in China, the authors present more than 40 key issues in a compact format suitable for time-constrained executives. The book covers the overall effects on the economy, highlights future challenges, gives first-hand advice on how to manage a business in China, and helps the reader to understand the Chinese culture. China Business 2.0 also contains valuable insight sections in which top executives and consultants share their on-the-ground-experiences in China. In addition, it features numerous practical tips that will help managers to be effective in China.